Chemical modification of β-cyclodextrins: balancing soft and rigid domains in complex structures - Luppi, Federico; Mai, Nathalie; Kister, Guillaume; Gill, Philip P.; Gaulter, Sally; Stennett, Christopher; Dossi, Eleftheria (Wiley, 2019)
Crystalline polymers such as β‐cyclodextrin (βCD) can be modified with polyethylene glycol (PEG) diglycidyl ether cross‐linkers (262, 394, 500 Da). Here we show that the quantity and length of the PEG soft segments influence the solubility and malleability of the products, which are water‐soluble and easily converted to nitrated analogues under standard reaction conditions. Inert and nitrated derivatives containing longer PEG segments showed the ability to self‐heal. The degree of cross‐linking and decomposition temperatures and energies depended on the quantity and length of the soft segment. Nitrated cross‐linked βCD containing longer PEG segments did not ignite following an electrostatic discharge of 4.5 J. The chemical stability of βCD/PEG binders was tested by heat flow calorimetry at 80 °C. We found that the balanced incorporation of soft PEG and rigid βCD segments improved the processability of cross‐linked βCDs and desensitised their nitrated derivatives, offering new solutions for inert and energetic binders.
Keywords: b-cyclodextrin; cross-linking; polyethylene glycol; inert binder; nitrated binder